Harnessing digital innovations to transform production and value chains in the spice industry - Prasath, D.; Sankar, S. Mukesh (Indian Horticulture, 2025)
Digitalization is transforming the spice industry, offering innovative solutions for production, supply chain optimization, and marketing. India, the largest producer and exporter of spices, is at the forefront of integrating emerging digital technologies such as sensors, drones, and mobile applications to enhance sustainability and precision in spice cultivation. Technologies like the Spice Vardatabase, decision support tools, and AI-driven quality assessments are improving farming practices, boosting productivity, and ensuring food safety. Additionally, blockchain technology and e-auction platforms like eSpice Bazaar and SPIISRY are streamlining trade and traceability, providing transparency in the spice supply chain. The adoption of these digital tools not only improves efficiency but also promotes eco-friendly and sustainable farming practices, benefiting producers, consumers, and the environment. As the industry continues to evolve, digital innovation will play a crucial role in maintaining the heritage of spices while adapting to modern market demands.